Censorship opposing viewpoints - Orr, Lisa 1966-. (San Diego, CA Greenhaven Press, 1990)
Presents opposing viewpoints about various aspects of censorship and freedom of speech. Includes critical thinking skill activities and a list of organizations to contact.
Includes bibliographical references (p. 230-232) and index.
Keywords: Censorship -- Juvenile literature; Censorship